2023
DOI: 10.1186/s13020-023-00849-y
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of traditional Chinese medicine for cancer-related fatigue: a systematic literature review of randomized controlled trials

Jingya Yang,
Yuxiao Li,
Chi Ian Chau
et al.

Abstract: Background Cancer-related fatigue (CRF) is an extremely common and long-term condition that affects the physical and mental health of oncology patients. While the treatment for CRF with western medicine and non-pharmacological therapy remains uncertain and challenging, traditional Chinese medicine (TCM) has become a trending option for the patients. Based on the findings from randomized controlled trials (RCTs), this study aims to identify and evaluate the evidence about the efficacy and safety… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 84 publications
(165 reference statements)
0
0
0
Order By: Relevance
“…The key ingredients of Buzhong Yiqi decoction include astragalus, codonopsis, white atractylodes, and chenpi. This ancient remedy has garnered recognition in modern medical studies for its remarkable anti-fatigue, immune-boosting, and anti-inflammatory properties among patients with spleen deficiency[ 5 ]. This study aimed to elucidate the impact of Buzhong Yiqi decoction on immune function and inflammatory markers in patients with spleen and stomach qi deficiency following laparoscopic radical surgery for colorectal cancer.…”
Section: Introductionmentioning
confidence: 99%
“…The key ingredients of Buzhong Yiqi decoction include astragalus, codonopsis, white atractylodes, and chenpi. This ancient remedy has garnered recognition in modern medical studies for its remarkable anti-fatigue, immune-boosting, and anti-inflammatory properties among patients with spleen deficiency[ 5 ]. This study aimed to elucidate the impact of Buzhong Yiqi decoction on immune function and inflammatory markers in patients with spleen and stomach qi deficiency following laparoscopic radical surgery for colorectal cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Cancer-related fatigue (CRF) is the most prevalent clinical symptom among cancer patients. 1 Studies have indicated that over 75% of cancer patients experience CRF, 2 with 25% to 30% of them enduring CRF for up to 10 years after cancer diagnosis. 3 , 4 CRF can be induced by the tumor itself or exacerbated by anti-tumor therapies, including radiotherapy, chemotherapy, and endocrine therapy.…”
Section: Introductionmentioning
confidence: 99%